Experimental and clinical observations on massive suprachoroidal hemorrhage. - Lakhanpal, V (1993)
We have been able to create a reproducible experimental model of nonexpulsive massive suprachoroidal hemorrhage in a rabbit eye. Massive suprachoroidal hemorrhage was demonstrated on echography and confirmed on histopathologic examination in all eyes. The natural course of the disease suggests that there is very little change in the size of the choroidal detachment in the first 7 days. Maximum liquefaction of the suprachoroidal hemorrhage clot was seen to occur between 7 and 14 days. However, increased retinal and ciliary body atrophy was also noted at 14 days. Therefore, the optimum time to drain massive suprachoroidal hemorrhage appears to be between 7 and 14 days. Immediate sclerotomy during the acute formation of massive suprachoroidal hemorrhage resulted in further increase in the suprachoroidal hemorrhage, with marked extension of the hemorrhage into the retina and vitreous. Therefore, in our opinion, immediate sclerotomy during massive suprachoroidal hemorrhage is detrimental to the eye. Our clinical data have shown that eyes with massive suprachoroidal hemorrhage can be treated successfully by secondary surgery, and the majority of the eyes can be salvaged with good visual results. No serious complications of this surgery were encountered in our cases. We advocate early surgical intervention between 7 and 14 days. Aggressive anterior and posterior segment reconstruction by anterior and posterior vitrectomy after sclerotomy drainage of the suprachoroidal hemorrhage is essential for better anatomic and visual results. Our animal data and clinical experience suggest that the optimum time of drainage of massive suprachoroidal hemorrhage is between 7 and 14 days. The results of our animal experiments in relation to human clinical application should be taken with caution. Furthermore, we had a small number of animals to study the various groups. In addition, longer follow-up may be needed for comparing controls with the treatment groups. Our animal model may help in such future studies on massive suprachoroidal hemorrhage.